Metaphors of language: the Vepsian ecology challenges an international paradigm - Siragusa, Laura (Eesti ja soome-ugri keeleteaduse ajakiri. Journal of Estonian and Finno-Ugric Linguistics, 2015)
At present Veps, a Finno-Ugric minority in north-western Russia, live in three different administrative regions, i.e., the Republic of Karelia, and the Leningrad and Vologda Oblasts. Due to several socio-economic and political factors Veps have experienced a drastic change in their communicative practices and ways of speaking in the last century. Indeed, Vepsian heritage language is now classified as severely endangered by UNESCO. Since perestroika a group of Vepsian activists working in Petrozavodsk (Republic of Karelia) has been promoting Vepsian language and culture. This paper aims to challenge an international rhetoric around language endangerment and language death through an analysis of Vepsian language ecology and revitalisation. Vepsian ontologies and communicative practices do not always match detached metaphors of language, which view them as separate entities and often in competition with each other. The efforts to promote the language and how these are discussed among the policy-makers and Vepsian activists also do not concur with such a drastic terminology as death and endangerment. Therefore, this paper aims to bring to the surface local ontologies and worldviews in order to query the paradigms around language shift and language death that dominate worldwide academic and political discourse.